The Relationship Between Sensory Marketing, Packaging, and Purchasing Decisions (a Study of Coffesia’s Coffee Product) - Gosal, Gladys Greselda; Sutrisno, Timotius F. C. W.; Filbert, Vincent (KnE Social Sciences, 2021)
Demand for coffee is growing, so it is not surprising that sensory marketing is often used to attract the consumer’s attention. This study aimed to determine the relationship between sensory marketing, packaging, and purchasing decisions of Coffesia’s coffee products, where sensory marketing focused on two factors: visual and touch. A survey method was used with 60 questionnaires distributed in the Surabaya region, but only 45 questionnaires were returned and processed. The Structural Equation Model - Partial Least Square (SEM-PLS) was used for data analysis. First, sensory marketing had a positive effect on purchasing decisions, which means it encouraged buyers to make purchasing decisions. Second, sensory marketing had a positive effect on packaging when buyers wanted to buy products with attractive packaging. Third, packaging had a positive effect on purchasing decisions. Finally, sensory marketing had a positive effect on purchasing decisions through packaging as a mediating variable. Keywords: sensory marketing, visual, touch, packaging, purchasing decision